Community Governance in Empowerment Transgender Community - Suntian, Isti Azhari Putri; Kushandajani, Kushandajani; Supratiwi, Supratiwi (Department of Government Studies, Universitas Syiah Kuala, 2025)
This study aims to determine the empowerment efforts undertaken by the Srikandi Transgender community towards a better quality of life inscription. The transgender group is closely related to discrimination, stigma and social powerlessness. Therefore, empowerment is present as a way out to achieve a better life. Community Governance or community governance comes from the limited access of the government as a public service agent that emphasizes collaboration with stakeholders. This study uses a descriptive qualitative research method with a focus on empowering efforts of the Srikandi Inscription community using a community governance perspective. The results of the study indicate that empowering efforts of Srikandi The inscription in a community governance perspective can lead the Srikandi The inscription community to an empowered condition. The collaboration process carried out by the Srikandi The inscription community with local agencies has produced good output for Srikandi Prasasti , including all community members having an Identity Card, Family Card, Birth Certificate, and Health Insurance Card. From a political perspective, all members of Srikandi The inscription can exercise their right to vote in general elections, both those that have taken place and those in the future. In this case, the Srikandi Prasasti community has succeeded in being empowered.